Empirical evaluation of sustainability of divergent farms in the dryland farming systems of India - Haileslassie, Amare; Craufurd, Peter Q.; Thiagarajah, R.; Kumar, S.; Whitbread, Anthony M.; Rathor, A.; Blümmel, Michael; Ericsson, P.; Kakumanu, Krishna Reddy (Elsevier, 2016)
The present study argues that there are heterogeneous farm systems within the drylands and each farmsystem is unique in terms of its livelihood asset and agricultural practice, and therefore in sustainability.Our method is based on household survey data collected from 500 farmers in Anantapur and KurnoolDistricts, in Andhra Pradesh State of India, in 2013. We carried out principal component analysis (PCA)with subsequent hierarchical clustering methods to build farm typologies. To evaluate sustainabilityacross these farm typologies, we adopted a framework consisting of economic, social and environmentalsustainability pillars and associated indicators. We normalized values of target indicators and employednormative approach to assign different weights to these indicators. Composite sustainability indices (CSI)were then estimated by means of weighted sum of indicators, aggregated and integrated into farm typolo-gies. The results suggested that there were five distinct farm typologies representing farming systemsin the study area. The majority of farms (>70%) in the study area are small and extensive (typology 1);marginal and off farm based (typology 2). About 20% of the farms are irrigation based and intensive (typol-ogy 3); small and medium and off farm based (typology 4) and irrigation based semi-intensive (typology5). There was apparent variability among farm typologies in terms of farm structure and functions andcomposite sustainability indices. Farm typologies 3 and 5 showed significantly higher performances forthe social and economic indices, while typologies 2 and 4 had relatively stronger values for environment.These discrepancies support the relevance of integrated farm typology- and CSI approaches in assessingsystem sustainability and targeting technologies. Universally, for all farm typologies, composite sustain-ability indices for economic pillar was significantly lower than the social and environment pillars. Morethan 90% of farmers were in economically less-sustainable class. The correlations between sustainabilityindices for economic and environment were typology specific. It was strong and positive when aggre-gated for the whole study systems [all samples (r = 0.183; P < 0.001)] and for agriculture dependent farmtypologies (e.g. typologies 1 and 3). This suggests the need to elevate farms economic performance andcapacitate them to invest in the environment. These results provide information for policy makers toplan farm typology–context technological interventions and also create baseline information to evaluatesustainability performance in terms of progress made over time.